The Effectiveness of Using Falou Application in Learning Speaking: An Experimental Study at SMKN 5 Mataram - Amrullah Amrullah; Husnul Lail; Nurtaat Lalu; M. Alfa Rhino (Program Studi Pendidikan Bahasa Inggris, 2026)
Digital technology, would have a significant impact on language learning with the use of mobile applications which play a major part in it. This has also facilitated students in SMKN 5 and above to improve their language skills beyond school hours. This study used a combination of experimental research designs. A total of 328 were tenth-grade students, and from those last-graded, forty were selected utilizing a random sample design. The subjects were divided into two groups the experimental group who used the Falou app and their control set which had traditional speaking lessons; they collected quantitive data through speaking tests before and after the lessons, along with interviewing participants and acquiring descriptive data from interviews/observation of classroom environments. The thematic analysis of numeric data was then examined descriptively through t-test revealing statistically significant improvements in speaking skills both in the experimental group and with practice with Falou app. Results indicated that the reported feeling was more self-confident and enthusiastic when using this application for practice. As a conclusion, this study represents that falou app as mobile information learning device has an effective improvement for oral language target students (vocational high school) to understand proficiently and have number of repetition on proffering with this application.